A low‐cost, mechanically simple apparatus for measuring eddy current‐induced magnetic fields in MRI. (22nd March 2013) - Gilbert, Kyle M.; Martyn Klassen, L.; Menon, Ravi S.
Abstract : The fidelity of gradient waveforms in MRI pulse sequences is essential to the acquisition of images and spectra with minimal distortion artefacts. Gradient waveforms can become nonideal when eddy currents are created in nearby conducting structures; however, the resultant magnetic fields can be characterised and compensated for by measuring the spatial and temporal field response following a gradient impulse. This can be accomplished using a grid of radiofrequency (RF) coils. The RF coils must adhere to strict performance requirements: they must achieve a high sensitivity and signal‐to‐noise ratio (SNR), have minimal susceptibility field gradients between the sample and surrounding material interfaces and be highly decoupled from each other. In this study, an apparatus is presented that accomplishes these tasks with a low‐cost, mechanically simple solution. The coil system consists of six transmit/receive RF coils immersed in a high‐molarity saline solution. The sensitivity and SNR following an excitation pulse are sufficiently high to allow accurate phase measurements during free‐induction decays; the intrinsic susceptibility matching of the materials, because of the unique design of the coil system, results in sufficiently narrow spectral line widths (mean of 19 Hz), and adjacent RF coils are highly decoupled (mean S 12 of −47 dB). The temporal and spatial distributions of eddy currents following a gradient pulse are measured to validate the efficacy of the design, and the resultant amplitudes and time constants required for zeroth‐ and first‐order compensation are provided. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : An apparatus was developed that consisted of six solenoid radiofrequency (RF) coils immersed in a high‐molarity saline solution. The RF coil system provides a low‐cost, mechanically simple solution to the measurement of transient magnetic fields caused by eddy currents. The apparatus was capable of measuring zeroth‐ and first‐order magnetic fields with high fidelity.